(untitled) (Research, Society and Development, 2021)
The Information Systems (IS) generate relevant information for organizational decision making. This study analyzes the contribution of the IS in the performance of the controllership, considering the activities listed in Resolution 0001/2009 of the Court of Auditors of the State of Pernambuco (TCE / PE), in a municipal government. Regarding the methodological procedures, the research is classified as applied, of an exploratory and descriptive nature, characterized as quantitative (cluster analysis) and qualitative (content analysis). The universe are all professionals (95), of the 14 control points, who work linked to the Municipal Comptroller General (CGM) of the Municipality studied. A semi-structured questionnaire and an interview script were used for data collection. Based on the data collected, the perceptions of the municipal controllers’ servers and managers about the tools provided by the SI were analyzed. The results show that IS contribute to all groups of controllership activities and that IS can contribute effectively to controllership, because when properly implemented, they are a strong indicator of efficiency and effectiveness in activities, especially those related to auditing. and decision making.